1995
DOI: 10.7326/0003-4819-122-5-199503010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil plus Levamisole as Effective Adjuvant Therapy after Resection of Stage III Colon Carcinoma: A Final Report

Abstract: Fluorouracil plus levamisole is tolerable adjuvant therapy to surgery; it has been confirmed to substantially increase cure rates for patients with high-risk (stage III) colon cancer. It should be considered standard treatment for all such patients not entered into clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
382
1
31

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 842 publications
(428 citation statements)
references
References 0 publications
12
382
1
31
Order By: Relevance
“…No clear trends were apparent in patients with Dukes' B2 disease. These results were confirmed in a later report after a median follow-up period of 6.5 years (Moertel et al, 1995 (Machover et al, 1986)] for 5 days every 28 days for six cycles. Of the 1493 evaluable patients, 736 were in the adjuvant treatment group and 757 were in the control (surgery only) group.…”
supporting
confidence: 69%
“…No clear trends were apparent in patients with Dukes' B2 disease. These results were confirmed in a later report after a median follow-up period of 6.5 years (Moertel et al, 1995 (Machover et al, 1986)] for 5 days every 28 days for six cycles. Of the 1493 evaluable patients, 736 were in the adjuvant treatment group and 757 were in the control (surgery only) group.…”
supporting
confidence: 69%
“…Ever since a randomized trial in the early nineties showed that patients with stage III colon carcinoma treated with adjuvant chemotherapy had a significant survival benefit [33], chemotherapy after surgery has been the standard of care for stage III patients with an adequate performance status. [10] However, not all patients with stage III disease receive adjuvant chemotherapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In CRC the prognostic predictor is tumour stage based on histopathologic examination of the resected specimen combined with perioperative findings (Dukes and Bussey, 1958;Lindmark et al, 1994;Fleming et al, 1997). It has been shown that adjuvant chemotherapy reduces the relative mortality rate by one-third in patients operated for colon cancer in Dukes' Stage C (any TN1-2M0, Stage III) (Moertel et al, 1995;Fleming et al, 1997). Adjuvant chemotherapy is not routinely given to patients of Dukes' Stage A (T1-2N0M0, Stage I) or Stage B (T3-4N0M0, Stage II) although a substantial number of patients with Dukes' Stage B tumour will die from tumour recurrences.…”
mentioning
confidence: 99%